Mathematics

Question

Find a - 2b + 3c diminished by a - 2b - 3c + d.

2 Answer

  • a - 2b + 3c -(a - 2b - 3c + d)

    =a - 2b + 3c -a + 2b + 3c - d

    =6c -d

  • Answer:  The required value is [tex]6c-d.[/tex]

    Step-by-step explanation:  We are given to find the following :

    [tex]a-2b+3c[/tex] diminished by [tex]a-2b-3c+d.[/tex]

    We know that

    the expression p diminished by q is written as "p - q".

    Therefore, the given expression implies

    [tex]a-2b+3c~\textup{diminished by}~a-2b-3c+d\\\\=(a-2b+3c)-(a-2b-3c+d)\\\\=a-2b+3c-a+2b+3c-d\\\\=6c-d.[/tex]

    Thus, the required value is [tex]6c-d.[/tex]

NEWS TODAY